Prediction of efficacy for conversion from adjunctive therapy to monotherapy with eslicarbazepine acetate 800 mg once daily for partial-onset epilepsy - Sunkaraneni S; Passarell JA; Ludwig EA; Fiedler-Kelly J; Pitner JK; Grinnell TA; Blum D (Dove Medical Press, 2017)
Soujanya Sunkaraneni,1 Julie A Passarell,2 Elizabeth A Ludwig,2 Jill Fiedler-Kelly,2 Janet K Pitner,1 Todd A Grinnell,1 David Blum1 1Sunovion Pharmaceuticals Inc., Marlborough, MA, USA; 2Cognigen Corporation (a SimulationsPlus company), Buffalo, NY, USA Purpose: Eslicarbazepine acetate (ESL) is a once-daily (QD) oral antiepileptic drug (AED) indicated for partial-onset seizures (POS). Clinical studies of gradual conversion to ESL 1,200 and 1,600 mg QD monotherapies were previously conducted in patients with POS who were not well-controlled by 1 or 2 AEDs. This report describes modeling and simulation of plasma eslicarbazepine (primary active metabolite of ESL) concentrations and time to monotherapy study exit to predict efficacy for conversion to ESL monotherapy at a lower dose of 800 mg, as an option for patients requiring or not tolerating higher doses since this regimen is effective in adjunctive therapy for POS. Patients and methods: A previously developed population pharmacokinetic model for ESL monotherapy was used to predict minimum plasma eslicarbazepine concentration (Cmin) in 1,500 virtual patients taking 1 (n=1,000) or 2 (n=500) AEDs at baseline, treated with ESL 400 mg QD for 1 week, followed by 800 mg QD for 17 weeks (similar to ESL monotherapy trials where the other AEDs were withdrawn during the first 6 weeks following titration to the randomized ESL dose). Model-predicted Cmin as a time-varying covariate and number of baseline AEDs were used to determine the weekly probability of each patient meeting exit criteria (65.3% threshold) indicative of worsening seizure control in 500 simulated ESL monotherapy trials. A previously developed extended Cox proportional hazards exposure–response model was used to relate time-varying eslicarbazepine exposure to the time to study exit. Results: For virtual patients receiving ESL monotherapy (800 mg QD), the 95% upper prediction limit for exit rate at 112 days of 34.9% in patients taking 1 AED at baseline was well below the 65.3% threshold from historical control trials, while the estimate for patients taking 2 AEDs (70.6%) was slightly above the historical control threshold. Conclusion: This model-based assessment supports conversion to ESL 800 mg QD monotherapy for POS in adults taking 1 AED. For patients taking 2 concomitant AEDs, however, prescribers should consider maintenance doses of 1,200 or 1,600 mg ESL QD to reduce the likelihood of seizure worsening if conversion to ESL monotherapy is contemplated. Keywords: eslicarbazepine, monotherapy, simulations, antiepileptic